Strategi Komunikasi Kim Malapeaka Dalam Mempromosikan Wisata Budaya Haroana Andala Di Kelurahan Bone-Bone Kecamatan Batupoaro - Aldiano, Muhamad Rasid; Suherman, Ansar; Nurfida, Wa (Innovative: Journal Of Social Science Research, 2024)
This This research aims to analyze KIM Malapeaka's communication strategy in promoting Haroana Andala Cultural Tourism in Bone-Bone Village, Batupoaro District, and identify the obstacles faced. Using descriptive qualitative methods, data was collected through observation, interviews and documentation. The results show that KIM Malapeaka adopted communication strategies such as social media, billboards, collaboration with journalists, and collaboration with influencers, which were effective in increasing public awareness. However, limited infrastructure and human resources are obstacles that need to be overcome to support long-term tourism growth.